2015
DOI: 10.1039/c5ra08824k
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive poly(methyl methacrylate) for bone fixation

Abstract: Poly(methyl methacrylate) (PMMA) is broadly used for bone fixation. One of the major concerns of using this polymer is the lack of post-implantation integration with the host tissue. We have produced a novel hybrid ceramic-thermoplastic composite manufactured by a sol-gel method via covalent bonding between bioactive glass and PMMA to address this shortcoming. The uniform distribution of bioactive glass promoted the bioactivity of PMMA and substantially improved the biological properties. In this paper, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Polymethacrylate can be copolymerized with methyl methacrylate (MMA) and 3-(trimethoxysilyl)­propyl methacrylate (TMSPMA) to produce an alkoxysilane containing polymer. Hybrids of poly­(MMA- co -TMSPMA) with a conetwork of SiO 2 have been investigated as biomaterials due to promising mechanical properties and bioactivity. However, the studies were more focused on macroscopic properties of the hybrids. The only variable investigated for the organic source was the TMSPMA content within the copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Polymethacrylate can be copolymerized with methyl methacrylate (MMA) and 3-(trimethoxysilyl)­propyl methacrylate (TMSPMA) to produce an alkoxysilane containing polymer. Hybrids of poly­(MMA- co -TMSPMA) with a conetwork of SiO 2 have been investigated as biomaterials due to promising mechanical properties and bioactivity. However, the studies were more focused on macroscopic properties of the hybrids. The only variable investigated for the organic source was the TMSPMA content within the copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…However, overcoming the brittleness issues of BGs [9,[14][15][16][17][18][19][20][21][22] comes at the cost of a significantly lower bioactivity compared with pure BGs [4,23]. For instance, the immersion of gelatin-siloxane or chitosan-siloxane hybrids in simulated body fluid (SBF) did not produce bone-like apatite formation on the hybrid surface for three weeks [19,24]. Similarly, existing hybrid materials only modestly stimulate the expression of osteogenicrelated gene markers such as phosphatase alkaline (ALP) activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, Chen et al demonstrated enhanced bioactivity of silicate bioceramic-PMMA composite compare to that of neat PMMA, 15 while results obtained by Ravarian et al showed that PMMA-bioactive glass composite supports osteoblast growth and differentiation. 20 Currently, a research trend is to fabricate scaffolds from bioceramic and polymer component with architectures mimicking the three-dimensional interconnected porosity of natural bone and an ability to guide cellular attachment and promote bone growth is one of the critical issues. 21 Here we present the synthesis of glass-ceramic (GC) powders and fabrication of GC-PMMA composite via polymerization induced by photoionization process.…”
Section: Introductionmentioning
confidence: 99%